"Be Strong My Sista'": Sentiments of Strength From Black Women With Chronic Pain Living in the Deep South. (28th February 2022) - Cousin, Lakeshia; Johnson-Mallard, Versie; Booker, Staja Q.
Abstract : The experience of chronic pain is influenced by gender, race, and age but is understudied in older Black women. Society and family alike expect Black older women to display superhuman strength and unwavering resilience. This qualitative study examined the narratives of 9 rural- and urban-dwelling Black older women to identify the ways in which they displayed strength while living with chronic osteoarthritis pain. Their " her stories" parallel the 5 characteristics of the Superwoman Schema/Strong Black Woman. Two additional characterizations emerged: spiritual submission for strength and code switching to suffering Black woman; these may be unique to Black Americans with pain.